GEOCHEMICAL FEATURES AND FACTOR MODELS OF THE BAZHENOV FORMATION IN THE CENTRAL AND SOUTHEASTERN REGIONS OF THE WEST SIBERIAN PLATE - E. A. Predtechenskaya; L. D. Malyushko (Известия высших учебных заведений: Геология и разведка)
The paper considers geochemical features of the Bazhenov Formation in the context of its petroleum potential and formation conditions. The major processes that had an impact on lithomineralogical and geochemical characteristics of the rocks were revealed by applying the G. Kharman’s factor analysis method. Four to eight factors were found that contributed to the formation of the current form of “bazhenites”. The main factors are facies environment of deposition and content of organic carbon, biogenic carbonate, and silica in deposits. Important factors were also mechanical differentiation of detritus in the sedimentary basin and autogenous mineral formation. The paper discusses possible reasons and results of unfavorable geochemical conditions that influenced the sedimentary strata (periodic contamination of bottom water by hydrogen sulfide, increased concentration of iron, cuprum, zinc, cadmium, and other toxic heavy metals and radioactive elements in deposits).